2A4U: A Visual Reward System Development - Abdul Manaf, Muhammad Munif; Ismail, Azniah (Journal of ICT in Education, 2021)
This paper describes a visual reward web-based system that can be used by parents to educate and motivate their children to achieve great performance in terms of good behavior and good academic achievement. Our research methodology was based on design and development research (DDR). We used the evolutionary prototyping model for the system development. To ensure that the system shall satisfy our targeted users, eight parents were involved in a few cycles of the development. Their requirements were collected through interviews and that information was used to build a prototype for the first cycle. The prototype was designed and developed based on a web-based architecture pattern. Then, in the following cycle, the prototype was used before the users’ feedback was collected, and the information was used to improve the prototype. Quantitative data were collected from respondents (parents) using a questionnaire, contained a 5-Likert scale and open-ended questions, right after they had tried the prototype on their children. In general, the findings showed that our users were satisfied with: (i) the clear user instruction feature (100%), (ii) the user interfaces, system navigation and flexibility (100%), (iii) the system ability (100%), (iv) the response time for displaying pages and saving data (87.5%), and (v) the contents provided were sufficient (75%). Our users also shared some of their experiences. In addition, we also found that the reward value exhaustion issue is real. Hopefully, our efforts through this system will encourage parents to be involved actively in nurturing, educating, and motivating their children, and create a healthy environment at home.